Factors affecting students’ academic performance in financial reporting course using framework-based teaching approach / Norilmiah Azis, Radziah Mahmud and Rosni Muda. - Azis, Norilmiah; Mahmud, Radziah; Muda, Rosni (2018)
Students’ performance (academic achievement) is fundamental in producing quality graduates. Many empirical studies are conducted to investigate factors affecting university students’ performance. The focus of this study is to measure the relationship between students and lecturers’ interaction, lecturers’ characteristics and lecturers’ knowledge and performance in financial reporting course using Framework-based Teaching Approach. The present study prefers a survey method. Questionnaires were used as instrument in this study and were distributed to students taking Advanced Financial Accounting and Reporting 1 (FAR610) during semester March-July 2017 at the Faculty of Accountancy, Universiti Teknologi MARA, Puncak Alam, Malaysia. Data were randomly selected dan analyzed using Statistical Package for Social Science (SPSS). Based on response from 91 students, the results show that only lecturers’ knowledge was positive and significantly related to financial reporting performance. The interaction of students and lecturers, and lecturers’ characteristics do not relate to the students’ performance in financial reporting course. The result will facilitate lecturers to understand and find new ways to be applied at the beginning of the course to improve students’ performance.